Further evidence for differences between cardiac atypical β-adrenoceptors and brown adipose tissue β3-adrenoceptors in the pithed rat - Malinowska, Barbara (1997)
1. We have previously shown (Malinowska & Schlicker, 1996) that the atypical β-adrenoceptor involved in the positive chronotropic effect of the so-called non-conventional partial β-adrenoceptor agonists CGP 12177 and cyanopindolol in the pithed rat possesses properties markedly different from those observed for β(3)-adrenoceptors in the literature. In the present study, we have directly compared the pharmacological properties of the atypical cardiostimulant β-adrenoceptor and of the β(3)-adrenoceptor mediating the thermogenic response in the brown adipose tissue in pithed and vagotomized rats. 2. Heart rate was dose-dependently increased by CGP 12177 and cyanopindolol by maximally 150 and 100 beats min(−1), yielding pED(50) values of 8.0 and 7.3, respectively (pED(50), −log(10) of the dose in mol kg(−1) body weight i.v. causing the half-maximum effect), but not affected by the selective β(3)-adrenoceptor agonist CL 316243 (pED(50)>6.0). 3. CGP 12177, cyanopindolol and CL 316243 increased temperature in the brown adipose tissue by maximally 1°C (pED(50) values 7.4, 6.3 and 8.6, respectively). 4. The β(1)-adrenoceptor antagonist CGP 20712 10 μmol kg(−1), attenuated the cardiostimulatory effect of CGP 12177 and, at a still higher dose (30 μmol kg(−1)), also antagonized its thermogenic effect. The −log(10) values of the doses causing a two fold shift of the dose-response curves (DRCs) of CGP 12177 to the right were 6.1 and 5.2, respectively, and were much lower than the corresponding value for the antagonism of CGP 20712 against the β(1)-adrenoceptor-mediated positive chronotropic effect which was 8.6. 5. The cardiostimulant and the thermogenic effect of CGP 12177 were not affected by the β(2)-adrenoceptor antagonist ICI 118551 10 μmol kg(−1). 6. The β(3)-adrenoceptor antagonist SR 59230A (which, by itself, caused a β(1)-adrenoceptor-mediated increase in heart rate and, for this reason, was studied after administration of a low dose of CGP 20712) attenuated the cardiostimulant and the thermogenic effect of CGP 12177 to a similar extent. The −log(10) values of the doses causing two fold rightward shifts of the DRCs of CGP 12177 were 5.9 and 5.7, respectively. 7. The non-selective β-adrenoceptor antagonist bupranolol diminished the cardiostimulant and thermogenic response to a very similar extent. The −log(10) values causing two fold rightward shifts of the DRCs of CGP 12177 were 5.6 and 5.7, respectively, and were much lower than the corresponding values for the antagonism of bupranolol against the β(1)-adrenoceptor-mediated positive chronotropic effect and the β(2)-adrenoceptor-mediated decrease in diastolic blood pressure which were 7.6 and 8.3, respectively. 8. The rank order of agonistic potencies for the cardiostimulant effect (CGP 12177>cyanopindolol > CL 316243) differs from that for the thermogenic response in the brown adipose tissue (CL 316243>CGP 12177>cyanopindolol); furthermore, there is a difference with respect to the rank orders of antagonistic potencies for cardiostimulation (CGP 20712⩾SR 59230A⩾bupranolol>ICI 118551) and thermogenesis (SR 59230A=bupranolol>CGP20712>ICI 118551). 9. In conclusion, our study provides further evidence that the atypical cardiostimulant β-adrenoceptors (causing an increase in heart rate) and β(3)-adrenoceptors are pharmacologically different.